Hope for “Continued Vitality”: Qualitative Study of Adults With Traumatic Brain Injury and Low Mood on Their Rehabilitation - Chui, Adora; Dainty, Katie N.; Kirsh, Bonnie; Dawson, Deirdre R.; Colquhoun, Heather (Frontiers in Rehabilitation Sciences, 2022)
Objective: Depression is highly comorbid with traumatic brain injury (TBI) with often complex and interacting symptomology that contributes to the experience of disability. Comorbid depression results in poorer TBI rehabilitation and downstream participation outcomes yet perspectives of this group regarding person-centred care is unknown. Purpose: This study aimed to explicate the perspectives of persons with TBI and depression on their values, preferences, and desired outcomes for optimal rehabilitation. Methods: A qualitative descriptive approach was taken. Thirteen adults (mean age: 40.5 [standard deviation 9.8]) diagnosed with TBI and with self-reported low mood were recruited through convenience sampling. Participants were predominantly female (n=12) with concussion/mild TBI and at least six months post-injury. One-on-one, semi-structured interviews were conducted by phone with Canadian participants (March-May 2020). Interviews were transcribed; data were analyzed thematically by two researchers and the thematic map refined by the research team. Results: Three themes were identified on values, preferences, and desired outcomes in person-centred care. Participants valued “validation” from healthcare providers and the health system to feel seen and believed about their conditions and concerns. They preferred for healthcare providers to “share the burden of managing care” through improved interactions and better access to concussion care. Participants expressed that “meaningful outcomes” were to be symptom free, to resume valued life activities, and to be able to adapt/be resilient. The latter indicated hope for “continued vitality” for life participation despite past and ongoing challenges. Conclusions: Many adults with TBI and self-identified low mood expressed rehabilitation experiences that were invalidating. Their identified values, preferences, and desired outcomes provide directions for better person-centred care by healthcare providers and health systems to support participation.